Analyzing the geomorphometric changes of Dana County due to the Sisakhat earthquake using the Differential Synthetic Aperture Radar Interferometry (D-InSAR) method. - Sayyd Morovat Eftekhari (تحقیقات کاربردی علوم جغرافیایی)
One of the consequences of the earthquake can be changes in the elevation levels of the unevenness in the area of occurrence. These changes at the level of the region will not be the same and the amount will be different under the influence of several factors such as: earthquake intensity, landforms, geo-material, and structure geological... The purpose of this research is to measure the geomorphometric changes caused by the earthquake of 17th February 2021 at the level of Dana County using the radar technique differential SAR Interferometry. To achieve this goal, taking into account the appropriate coverage and measurement accuracy of the Sentinel 1 radar satellite images from two image scenes related to the earthquake area for the dates before (2021.02.08) and after the earthquake (2021.02.20) from the organization's website. European Space Agency (ESA) was received, after performing the process and data analysis Differential Synthetic Aperture Radar Interferometry (D-InSAR), it was found that after the earthquake dated 2021,02,17, a part of the studied area was affected by positive elevation changes with a rise of 0.11 cm and Negative changes of -0.6 cm subsidence have been encountered. These positive changes (uplift) are more noticeable near the epicenter of the earthquake in the east of Dena, and the negative changes (subsidence) are quite evident with the Syncline Valley on which Khorasan Rivers is located. And in dealing with the faults, changing the geological structure, geo-material of the region, it has a special irregularity.